37.8k views
5 votes
I need to simplify this problem as much as I can. But I’m confused I just need step for step then the answer

I need to simplify this problem as much as I can. But I’m confused I just need step-example-1

1 Answer

3 votes


\bf \textit{Pythagorean Identities} \\\\ sin^2(\theta)+cos^2(\theta)=1\implies cos^2(\theta )=1-sin^2(\theta ) \\\\[-0.35em] ~\dotfill\\\\ \cfrac{sin^2(\theta )}{1-sin^2(\theta )}\implies \cfrac{sin^2(\theta )}{cos^2(\theta )}\implies \left[ \cfrac{sin(\theta )}{cos(\theta )} \right]^2\implies tan^2(\theta )

User Billcyz
by
3.9k points